Organiser - Koureas, Gabriel (My University, 2026)
Event inspired by the poetry of Elias Konstantinou on World AIDS Day at the Cyprus University of Technology in collaboration with independent group CEL, December 01, 2021, Cyprus University of Technology, Limassol, Cyprus. event inspired by the poetry of Elias Konstantinou on World AIDS Day at the Cyprus University of Technology in collaboration with independent group CEL, December 01, 2021, Cyprus University of Technology, Limassol, Cyprus. https://www.youtube.com/watch?v=b9BgPz5tpYA